COVID-19 infections in infants - Małgorzata Sobolewska-Pilarczyk; Maria Pokorska-Śpiewak; Anna Stachowiak; Magdalena Marczyńska; Ewa Talarek; Agnieszka Ołdakowska; Izabela Kucharek; Adam Sybilski; Anna Mania; Magdalena Figlerowicz; Katarzyna Mazur-Melewska; Paulina Potocka; et al. (Scientific Reports, 2022)
Abstract The study aimed to analyse the clinical course of COVID-19 in 300 infants, selected from 1283 children diagnosed with COVID-19 between March and December 2020, registered in the SARSTerPED multicenter database. Most of the infants were registered in October and November 2020. 44% of the group were girls, and 56% were boys. At diagnosis, the most common symptoms were fever in 77% of the children, cough in 40%, catarrh in 37%. Pneumonia associated with COVID-19 was diagnosed in 23% of the children, and gastrointestinal symptoms in 31.3%. In 52% of the infants, elevated levels of D-dimers were observed, and in 40%, elevated levels of IL-6 serum concentration were observed. During the second wave of the pandemic, 6 times more infants were hospitalized, and the children were statistically significantly younger compared to the patients during the first wave (3 months vs 8 months, p < 0.0001 respectively). During the second wave, the infants were hospitalized for longer. COVID-19 in infants usually manifests as a mild gastrointestinal or respiratory infection, but pneumonia is also observed with falls in oxygen saturation, requiring oxygen therapy. Gastrointestinal symptoms are common in infants infected with SARS-CoV-2, and infant appetite disorders may lead to hospitalization. The clinical course of the disease differed significantly between the first and second wave of the pandemic. It seems that infants may play a role in the transmission of SARS-COV-2 infections in households, despite mild or asymptomatic courses; eating disorders in infants should be an indication for COVID-19 testing.